Designing a Multipurpose Production Cluster - Neeman, Henry (My University, 2015)
"Designing a Multipurpose Production Cluster" presented to the Linux Cluster Institute Workshop on May 22, 2015 by Dr. Henry Neeman
Henry Neeman, University of Oklahoma Assistant Vice President, Information Technology - Research Strategy Advisor Director, OU Supercomputing Center for Education & Research (OSCER) Associate Professor, College of Engineering Adjunct Faculty, School of Computer Science
Keywords: Computer Science